Persepsi Mahasiswa Terhadap Penggunaan Media Online Dalam Pembelajaran Bahasa Arab Selama Pandemic Di Perguruan Tinggi - Aulia, Ayu; Hamidah, Hamidah; Ilmiani, Aulia Mustika (Institut Agama ISlam Negeri Palangka Raya, 2023)
As a result of this policy, many sectors were paralyzed, one of them is the education sector. As a result of this pandemic, school and even universities transferred to online learning using various methods facilities and applications as well as websites. One such application is Zoom Meeting, Google Classroom, Google Meet, WhatsApp and many more other applications. The purpose of this research is to know the students perceptions about the use of online media in learning Arabic during pandemic in college. This research method is descriptive quantitative. Data collection was carried out using a questionnaire on student perceptions of use of online media. Data analysis using statistical data analysis descriptive by using the average. The results of this study indicate that the Zoom Meeting media scores the total is 12,51. On Google Classroom media 8,96. On Google Meet media 6,12. On WhatsApp media 5,59. So the average score (Mean) the end of the total amount of data obtained is 33,18 : 11 = 3,01 which are on an interval scale of 2,62